Dispersion of ZrO2 and Y2O3 nanopowders in physiological suspensions; Journal of Physics: Conference Series; Vol. 304 : Nanosafe 2010 - Godymchuk (Godimchuk) A. Yu. Anna Yuryevna; Arzamastseva E. Yu. Evgeniya Yurievna; Kuznetsov D. V. Denis Valerjevich; Milyaeva S. I. Svetlana (2011, 2011)
Title screen